2013
DOI: 10.4236/asm.2013.31001
|View full text |Cite
|
Sign up to set email alerts
|

“They Will Wonder What Kind of a Girl I Am”: Adolescent Perceptions towards Contraceptive Use in Nairobi

Abstract: As in other developing countries, contraceptive use among adolescents is low and only one in twenty adolescents is reported to use contraceptives in Kenya. Pregnancies early in life expose adolescents to health complications. Establishing perceptions that affect contraception and factors that influence those perceptions is important in developing appropriate programs and policies to increase contraceptive use prevalence among adolescents. We used primary data from a household survey using a systematic random s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 18 publications
3
12
1
Order By: Relevance
“…Although some were positive, the predominant perceptions were negative, showing some ignorance and a tendency to blame others. Syed et al ( 2012 :2–5), Appiah-Agyekum and Kayi ( 2013 :41–42) and Kinaro ( 2013 :7) are in agreement with the findings that contributed to the non-use and the discontinued use of contraceptives.…”
Section: Discussionsupporting
confidence: 77%
“…Although some were positive, the predominant perceptions were negative, showing some ignorance and a tendency to blame others. Syed et al ( 2012 :2–5), Appiah-Agyekum and Kayi ( 2013 :41–42) and Kinaro ( 2013 :7) are in agreement with the findings that contributed to the non-use and the discontinued use of contraceptives.…”
Section: Discussionsupporting
confidence: 77%
“…Further, the youth believed in having unprotected sex when they were still young. These findings are consistent with theory of perception formation on barriers to contraceptive use [30] [31]. These myths influence contraceptives use and expose youth to unprotected sex hence risk to sexually transmitted diseases including unwanted pregnancies.…”
Section: Discussionsupporting
confidence: 89%
“…There is need to develop behavior change communication materials that encourage partner communication on SRH issues for the community.One of the key needs mentioned by adolescents and youth was to know how condoms are used. Studies show that contraceptive use increases with the level of knowledge of how they are used[29] [30]. A study in Kenya found that use of contraception was significantly higher among adolescents 15 -19 years who…”
mentioning
confidence: 99%
“…In addition, unmarried adolescents are less likely to use modern hormonal contraceptives than their older female counterparts [ 4 ]. This has led to a high fertility rate among adolescents in Kenya, ranging from 2% at age 15 to 36% at age 19 [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among adolescents living with HIV, avoiding unintended pregnancy reduces vertical transmission of HIV and maternal mortality associated with HIV infection [ 10 ]. Increasing contraception use among all adolescent females has also been associated with greater female empowerment and enhanced educational and economic opportunities, and adolescent females living with HIV using contraception may garner similar benefits [ 8 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%